Laser Raman and Infrared Spectra of 3-Cyanopyridine - Isaq, M.; Gupta, S.P.; Sharma, S.D.; Ahmad, S. (Asian Journal of Chemistry, 2010)
The Laser Raman and IR spectra of 3-cyanopyridine have beenreported along with their assignments. An assignment of fundamentalsis proposed and comparison with similar molecules is discussed.